Parent`s knowledge of their children`s oral status - Holm, Mia Jung; Christensen, Camilla Celise (Universitetet i Tromsø, 2013)
Abstract Background: Good oral habits in early childhood is essential for the maintenance of the primary teeth. This is important to ensure a high quality of dental health troughout life. An important key to accomplish this is to make sure that parents have a sincere interest and good knowledge concerning their children´s oral status as well as their preventive oral care. Aims: Determine parents´s knowledge about their child´s oral status and preventive home care habits in Ankenes and Hammerfest. Materials and methods: This study was conducted as an epidemiological pilot-study on parents to a child between the age of 5 and 8. The study was performed during the external practice in the 7th semester. The sample consisted of 63 parents, 36 from Ankenes and 27 from Hammerfest. Data were collected using a questionnaire and the children´s dental records. Results: The mean age of the total number of children was 6,1 years and the study showed that 79% of the children had no restorations. The parents´ knowledge level regarding oral status was similar in the two towns. Only 63% of the parents were able to place their child in the correct "5-tooth-interval" regarding number of teeth, while the percentage of correct answers concerning the number of restorations was considerably higher (90%). The results showed that parents from both towns had a higher knowledge-level concerning the number of permanent teeth compared to the number of primary teeth. The parents´ knowledge concerning oral health promoting measures seemed to be good in general, but they were not always able to accomplish that knowledge when it came to consumption of candy and soft drinks. None of the children, however, was eating candy daily, whereas four children drank soft drinks or juice every day. Comparing the two towns, it was significantly more common for the parents in Ankenes to always help their children during tooth brushing, while fluoride tablets was provided significantly more often in Hammerfest. Conclusion: It had to be considered poor parental ...